Dual-beam interferometric particle imaging for size and shape characterization of irregular coal micro-particle: Validation with digital inline holography. (January 2020) - Wu, Xuecheng; Shi, Lin; Lin, Zhiming; Wu, Yingchun; Brunel, Marc; Jacquot, Justin; Gréhan, Gérard
Highlights: Dual-beam interferometric particle imaging (DIPI) is applied to irregular particle. Digital inline holography (DIH) and DIPI signals separate in channels of RGB image. The accuracy of size and shape measurement with DIPI is evaluated referring to DIH. Graphical abstract: Abstract: The size and shape characterization of irregular particles is of great significance in the comprehensive understanding of many natural and industrial processes. The dual-beam interferometric particle imaging (DIPI) technique is adapted from a dual-beam backward illumination configuration of interferometric particle imaging to access the size and 2D shape of an irregular particle from its interferogram. An experimental setup combining the digital inline holography (DIH) and DIPI techniques characterizes the same projection of the same particle with a color camera, permitting the accuracy evaluation and validation between these two techniques. The comparison results show a good agreement between the 2D-Fourier transform of DIPI interferogram and the 2D-autocorrelation of DIH reconstructed in-focus image. The DIH gives the reference result for the size measurement of the particles, and we observe a maximum difference as low as 9% with the DIPI measurement. The backward arrangement of the dual-beam interferometric particle imaging technique facilitates its further instrumental development and application to a variety of real circumstances, e.g., solid fuel particles and ice crystals.